Q: Can you factor 2x plus 6?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

You would factor 2x2 + 7x + 6 into (2x + 3) (x+2)

8

(3x + 2)(2x + 3)

2(x^2 +2x + 3)

-x2 + 2x + 48 = (-x - 6)(x - 8) = -(x + 6)(x - 8)

Related questions

You would factor 2x2 + 7x + 6 into (2x + 3) (x+2)

2x+12=2(x+6)

2x(x^2+x-6)

(2x - 3)(x + 2)

8

(3x + 2)(2x + 3)

(x - 2)(2x - 3)

2(x^2 +2x + 3)

-x2 + 2x + 48 = (-x - 6)(x - 8) = -(x + 6)(x - 8)

2x2 + 7x + 6 = 2x2 + 4x + 3x + 6 = 2x(x + 2) + 3(x + 2) = (x + 2)(2x + 3)

2(x+3)

2(x + 3)(x + 1)